Strategi Pengendalian Biaya dan Hambatan Adaptasi Akuntansi Manajemen pada UMKM Makanan Olahan di Tangerang Selatan - Yandi Asmana (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
Small and medium-sized enterprises (SMEs) in the processed food sector in South Tangerang face complex challenges in cost control due to raw material price fluctuations, urban market competition, and logistical constraints. This qualitative phenomenological study examines the strategies and barriers in adapting management accounting systems among 15 SMEs partnered with STIE Ganesha (January–March 2025). Data were collected through in-depth interviews, participatory observation, and document analysis, then analyzed thematically. Findings reveal three key strategies: (1) collective raw material procurement (15–20% cost efficiency), (2) flexible labor allocation, and (3) use of simplified cost-of-goods-sold (COGS) applications. However, 60% of SMEs struggled to integrate overhead costs into bookkeeping due to limited accounting literacy and the absence of structured systems. These findings enrich contingency theory by demonstrating the misalignment of traditional accounting systems with the dynamics of urban SMEs. The study recommends developing mobile-based accounting training modules, fostering university-government collaboration for digital tool provision, and implementing sustained mentoring programs. A key limitation is the sample’s restriction to campus-partnered SMEs.